Conversion strategies for Dutch primary schools: practice and refinement - Broekhuizen, Dolf; Arkesteijn, Monique; Jong, Peter de; Nieuwamerongen, Frido van (Journal of Architecture and Urbanism, 2020)
Handbooks on strategic real estate management are generally based on four strategies for functional adjustment of the building: conversion, expansion, renovation and adaptive reuse. And on a strategic level, this classification in adjustment strategies does work for real estate in general. But when looking at Dutch primary schools as a specific type of real estate, reality can be and is more nuanced. Other accommodation strategies came to the fore in a study into the spatial adaptation of primary schools and children’s centres in the Netherlands. An analysis of 100 school buildings studied in the Atlas of School Building (published in Dutch as Scholenbouwatlas) revealed that nine main strategies were prevalent in practice. This refinement of the strategies fits (better) with integrated conversion actions of primary schools in which several aspects are solved together. In the following article these strategies are analysed and discussed in a theoretical context. The conclusion of the analyses is that the existing general models in the strategic handling of the building stock in the case of specific real estate of primary schools can be refined.